Improving Nursing Knowledge of Alcohol Withdrawal: Second Generation Education Strategies. Issue 6 (November 2015) - Berl, Kimberly; Collins, Michelle L.; Melson, Jo; Mooney, Ruth; Muffley, Cheryl; Wright-Glover, Angela
Abstract : Christiana Care Health System implemented a Care Management Guideline for Alcohol Withdrawal Symptom Management, which provided direction for inpatient screening for alcohol withdrawal risk, assessment, and treatment. Nurses educated on its use expressed confusion with the use of the assessment tools, pharmacokinetics, and pathophysiology of alcohol withdrawal and delirium tremens. Reeducation was provided by nursing professional development specialists. Pre- and postsurveys revealed that nurses were more confident in caring for patients with alcohol withdrawal.